Building construction on ex-mining land / Siti Rahayu Yaakub - Yaakub, Siti Rahayu (2003)
Malaysia has very good potential in construction development. The demand for the industrial building, commercial and housing also increased. The area that having high commercial value is limited at the Malaysia city center nearby the ex-mining land area such as Selangor state. To solve the land problem, the developer changed the shape of the developement from the land to the ex-mining reclamation project for various building like industrial building, commercial and housing building.